The Influence Of Thinking Styles and Mathematical Beliefs On The Elementary Mathematics Teacher’s Communication Ability - Alifa Sabrina; Suyono Suyono; Wardani Rahayu (Mathematics Education Study Program, 2019)
The aim of the research was to determine the influence of thinking styles and mathematical beliefs of Elementary Mathematics Teacher according to their mathematics communication ability. The participants were 60 elementary teachers in UPBJJ-UT (Terbuka University) Jakarta. They were chosen as a sample with simple random sampling technique, where the test was held in June 14, 2015. The Multiple Linier Regression was used to analyzed the data, where the instruments consist mathematics communication, thinking styles and mathematical beliefs. Based on the value of R square applied in the SPSS, showed that there is 0.457 or 45.7% the influence of mathematical beliefs and thinking styles according to the mathematics communication in students in Elementary Teacher Studies program in UPBJJ-UT Jakarta.